MUSYAWARAH PROVINSI POBSI KALIMANTAN SELATAN - H. Noor Fathulliansyah1 (Akademi Maritim Nusantara Banjarmasin, 2022)
AbstractImplementation is an activity that has been prepared in accordance with the program andobjectives, with the implementation of the Musprov it is expected to find a qualified generalchairman and sports administrator so that in the future it will give birth to professional athletesand become a means for athletes in the South Kalimantan region in developing talent towards aprofessional direction.Keywords: implementation, culture, economy